Gambaran Kelelahan Pada Nelayan Di Desa Waisarissa Kecamatan Kairatu Barat Kabupaten Seram Bagian Barat - Ellen Lombonaung; Maryam Lihi (Jurnal Rumpun Ilmu Kesehatan, 2022)
Fatigue is a problem that needs attention. All types of work both formal and informal cause fatiguehWork. Fatiguehwork will reduce performance and increase work errors. Fishermen are one of the marine communities that need to receive government attention in the health sector, namely fishermen, because fishermen's work is dangerous to health. The purpose of this study was to describe work fatigue in fishermen in Waisarisa Village, Kairatu Barat District, West Seram Regency. The type of research used is descriptive research. with a total sample of 20 respondents. By way of sampling, namely Total Sampling. The data that has been collected is then tabulated in a table according to the variable to be measured. Data analysis was carried out through the stages of editing, coding, tabulation and statistical testing. The statistical test used was univariate. The results showed that 12 people (60%) had a work attitude that was considered the most at risk, and 35% had work fatigue. It was concluded that what can be described in this study shows that work attitudesrespondentor fisherman is best described with a heavy risk attitude. And in the most fatigue described there are respondents who experience a lot of fatigue at work.